Al Film Electrodeposition from the AlCl3-EMIC Electrolyte under a Magnetic Field. Issue 8 (1st January 2017) - Takahashi, Hitomi; Matsushima, Hisayoshi; Ueda, Mikito
Abstract : The surface structure of Al films electrodeposited in a magnetic field was studied in a AlCl3 -1ethyl-3methylimidazolium chloride (EMIC) mixture ionic liquid, focusing on the surface morphology and crystal orientation. Current-dependent measurements reveal two preferential orientations. First, at small current densities ( i < 10 mA cm −2 ), a (111) plane is preferentially oriented parallel to the surface where no magnetic field is detected. Second, at high current densities ( i > 10 mA cm −2 ), a (200) plane is selectively grown, where the mass transportation of Al(III) is promoted by magneto-hydrodynamic (MHD) convection. Correlations of these data with scanning electron microscope observations showing tabular-facet formation in the magnetic field suggest that these structural variations are induced by microscopic MHD, demonstrating the difference between this process and that existing in an aqueous system.